Electrocatalytic hydrogenation of cyanoarenes, nitroarenes, quinolines, and pyridines under mild conditions with a proton-exchange membrane reactor - Mitsudo, Koichi; Osaki, Atsushi; Inoue, Haruka; Sato, Eisuke; Shida, Naoki; Atobe, Mahito; Suga, Seiji (Beilstein Journal of Organic Chemistry, 2024)
An electrocatalytic hydrogenation of cyanoarenes, nitroarenes, quinolines, and pyridines using a proton-exchange membrane (PEM) reactor was developed. Cyanoarenes were then reduced to the corresponding benzylamines at room temperature in the presence of ethyl phosphate. The reduction of nitroarenes proceeded at room temperature, and a variety of anilines were obtained. The quinoline reduction was efficiently promoted by adding a catalytic amount of p-toluenesulfonic acid (PTSA) or pyridinium p-toluenesulfonate (PPTS). Pyridine was also reduced to piperidine in the presence of PTSA.
Keywords: cyanoarene; nitroarene; PEM reactor; pyridine; quinoline